2022 Qatar World Cup: A Netnographic Analysis of the Relationship Between Sport, Media and Politic - Abdelmajid LAMSIAH; Badr BENTALHA (Réflexions Sportives)
Sporting events have always been an opportunity to exhibit the power of sports to strengthen cultural relations, promote political interconnection, and consolidate social acceptance. The aim of this research is to understand why and how internet users engage differently with the proposal and acceptance of the hosting of a World Cup, namely Qatar 2022. An online netnographic survey was conducted to identify the perceptions of internet users on the organization of the Qatar 2022 World Cup.